Characterization and Analysis of the Temporal and Spatial Dynamic of Several Enteritis Modeling Methodologies - Xu, Huangru; Cai, Fangfang; Li, Ping; Wang, Xiaoyang; Yao, Yingying; Chang, Xiaoyao; Bi, Zhiqian; Sun, Huisong; Zhuang, Hongqin; Hua, Zi-Chun (Frontiers in Immunology, 2021)
Inflammatory bowel disease (IBD), including Crohn’s disease and ulcerative colitis, is a complex disease involving genetic, immune, and microbiological factors. A variety of animal models of IBD have been developed to study the pathogenesis of human IBD, but there is no model can fully represent the complexity of IBD. In this study, we established two acute enteritis models by oral 3% DSS or intraperitoneal injection of anti-CD3 antibody, and two chronic enteritis models by feeding 3 cycles of 1.5% DSS or 3 months of the high-fat diet, respectively, and then examined the clinical parameters, histological changes, and cytokine expression profiles after the successful establishment of the models. Our results indicated that in 3% DSS-induced acute enteritis, the colorectal injury was significantly higher than that of the small intestine, while in anti-CD3 antibody-induced acute enteritis, the small intestine injury was significantly higher than that of colorectal damage. Besides, in the 1.5% DSS-induced chronic enteritis, the damage was mainly concentrated in the colorectal, while the damage caused by long-term HFD-induced chronic enteritis was more focused on the small intestine. Therefore, our work provides a reference for the selection of appropriate models when conducting research on factors related to the pathogenesis of IBD or evaluating the potential diagnosis and treatment possibilities of pharmaceuticals.